Expression of adrenomedullin in human colorectal tumors and its role in cell growth and invasion in vitro and in xenograft growth in vivo. (29th January 2013) - Nouguerède, Emilie; Berenguer, Caroline; Garcia, Stéphane; Bennani, Bahia; Delfino, Christine; Nanni, Isabelle; Dahan, Laetitia; Gasmi, Mohamed; Seitz, Jean‐François; Martin, Pierre‐Marie; Ouafik, L'Houcine
Abstract Adrenomedullin (AM) is a multifunctional peptide vasodilator that transduces its effects through calcitonin receptor‐like receptor/receptor activity‐modifying protein‐2 and ‐3 (CLR/RAMP2 and CLR/RAMP3). In this study, real‐time quantitative reverse transcription demonstrated a significant expression of AM mRNA in tumor samples from colorectal cancer (CRC) patients in clinical stage II, III, and IV when compared with normal colorectal tissue. AM, CLR, RAMP2, and RAMP3 proteins were immunohistochemically localized in the carcinomatous epithelial compartment of CRC tissue. Tissue microarray analysis revealed a clear increase of AM, CLR, RAMP2, and RAMP3 staining in lymph node and distant metastasis when compared with primary tumors. The human colon carcinoma cells HT‐29 expressed and secreted AM into the culture medium with a significant increase under hypoxia. Treatment of HT‐29 cells with synthetic AM stimulated cell proliferation and invasion in vitro. Incubation with anti‐AM antibody (αAM), anti‐AM receptors antibodies (αAMR), or AM antagonist AM22–52 inhibited significantly basal levels of proliferation of HT‐29 cells, suggesting that AM may function as an autocrine growth factor for CRC cells. Treatment with αAM significantly suppressed the growth of HT‐29 tumor xenografts in vivo. Histological examination of αAM‐treated tumors showed evidence of disruption of tumor vascularity with decreased microvessel density, depletion of endothelial cells and pericytes, and increased tumor cell apoptosis. These findings highlight the potential importance of AM and its receptors in the progression of CRC and support the conclusion that αAM treatment inhibits tumor growth by suppression of angiogenesis and tumor growth, suggesting that AM may be a useful therapeutic target.